Parkinsonismo y habilidades visoperceptuales: Revisión bibliográfica (2021)
The scope of this research work is to analyze the visuoperceptual abilities in parkinsonism, a condition defined as: the pathophysiological state resulting from the loss of substantia nigra and the dopaminergic alteration of the basal ganglia that manifests as bradykinesia, muscle rigidity, tremor in the body and disorders in postural balance (1). There are various types of parkinsonism, of which, at present, its cause is not completely clear; however, it has been described that they mainly affect the patient's motor capacity with a worldwide prevalence of more than 3% in patients older than 65 years.